Characterization of the illumination of the regeneration microsites of 14 tree species in an intervened humid forest in Costa rica and the effect of intervention on the abundance of natural regeneration - Díaz Gonzáles, J.C. (1995)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995